Effect of Irrigation on the Changes in Wetland Rice Productivity (Oryza Sativa L.) due to a Climate Change in North Sumatra Province - Hasbul Hadi; Diana Chalil (Indonesian Journal of Agricultural Research, 2018)
Climate change is one of serious threats to the agricultural sector. In North Sumatra Province, climate change is characterized by shorter rainy season with higher rainfall. To overcome such climate change, it is necessary to provide irrigation that can accommodate excessive rain water and distribute it in times of shortage. Therefore, changes in rainfall will not be too influential on productivity. This is especially important for plants that need a lot of water like rice. To analyze the influence of irrigation in North Sumatra Province, the data were collected from 27 regencies/cities in 2011-2015 and were analyzed using a Simple Linear Regression analysis model. The estimation results show that irrigation can push the productivity variances. The irrigation regression coefficient of -0.133432 shows that each increase of irrigation area by 1% will decrease the productivity variation by 0.13 tons/ha